2022
DOI: 10.1002/uog.24842
|View full text |Cite
|
Sign up to set email alerts
|

Evolving fetal phenotypes and clinical impact of progressive prenatal exome sequencing pathways: cohort study

Abstract: What are the novel findings of this work?In this preliminary cohort study, the National Health Service (NHS) England R21 prenatal exome sequencing pathway provided a unifying genetic diagnosis in over 50% of preselected cases with a structural anomaly on prenatal ultrasound. What are the clinical implications of this work?Prenatal exome sequencing using the NHS England R21 pathway can provide diagnostic information in fetuses with a structural malformation. It is important to monitor fetal phenotype throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 26 publications
1
41
1
Order By: Relevance
“…We thank Drs Li and Li for their comments on our recent study 1 . Our paper highlights the challenges of introducing a prenatal exome sequencing (ES) service into a clinical pathway within the National Health Service (NHS) in England and demonstrates that pretest multidisciplinary discussion within a designated fetal medicine/genetics clinic and sequential ultrasound scans to define the fetal phenotype lead to optimal clinical utility.…”
Section: Replymentioning
confidence: 98%
“…We thank Drs Li and Li for their comments on our recent study 1 . Our paper highlights the challenges of introducing a prenatal exome sequencing (ES) service into a clinical pathway within the National Health Service (NHS) in England and demonstrates that pretest multidisciplinary discussion within a designated fetal medicine/genetics clinic and sequential ultrasound scans to define the fetal phenotype lead to optimal clinical utility.…”
Section: Replymentioning
confidence: 98%
“…Mone et al . reported that ES had a significant clinical impact in 78.3% (18/23) of cases in which a causative pathogenic variant was detected 5 . Why did the test results have no clinical impact in 21.7% (5/23) of patients and what were the ES results of these patients?…”
Section: Figurementioning
confidence: 99%
“…Mone et al . recently reported their initial experience in the application of R21 pathway 5 . Of the 54 included cases, 25 underwent prenatal trio ES following selection by a multidisciplinary team (pre‐R21) and 29 had prenatal trio ES based on the NHS England R21 pathway, with deep phenotyping performed throughout pregnancy and postnatally.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Clinical diagnostic yield was relatively low at 10–12% overall. Selection of cases using a ‘pre-test’ multidisciplinary team (including a Clinical Geneticist) and careful ‘targeting’ of specific fetal phenotypes may significantly increase diagnostic rate to over 30% [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%